PENGARUH PENGGUNAAN MEDIA SANDPAPER LETTERS TERHADAP KEMAMPUAN MENGENAL HURUF ANAK DOWN SYNDROME DI SLB BHAKTI KENCANA I - Perdana Saputra, Nova; Noormiyanto, Faiz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children with Down syndrome often experience delays in language development, particularly in recognizing alphabet letters, which become the foundation of early literacy skills. Appropriate instructional media are therefore needed to provide meaningful and multisensory learning experiences. This study aimed to determine the effect of Sandpaper Letters media on the letter recognition ability of children with Down syndrome at SLB Bhakti Kencana I. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The research participants consisted of five students with Down syndrome selected through total sampling. Data were collected using a letter recognition performance test consisting of 15 validated items covering the abilities to identify, name, distinguish, match, and recall letters. Data analysis was conducted using descriptive statistics and the Wilcoxon Signed-Rank Test with IBM SPSS Statistics. The findings indicated an increase in students' mean scores from 25.20 on the pretest to 51.60 on the posttest. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.043, which was lower than the significance level of 0.05, indicating a statistically significant difference between pretest and posttest scores. These findings demonstrate that the use of Sandpaper Letters media significantly improves the letter recognition ability of children with Down syndrome. Therefore, Sandpaper Letters can be considered an effective multisensory learning medium to support early literacy instruction for children with special educational needs.